A Study of the Inmate Code of Conduct in Spanish Prison. Issue 12 (2nd December 2021) - Penado Abilleira, Maria; Rodicio-García, María Luisa
ABSTRACT: The adaptation to life within the prisons is still unknown today despite having been defined almost 80 years ago by Clemmer under the name of prisonization. The aim of this paper is to estimate the phenomenon of prisonization in the Spanish penitentiary environment through a sample of 509 inmates. For data collection an instrument has been developed of the estimation of the prisonization. Correlation and regression analyzes have been carried with variables of both importation and deprivation models of prisonization. As a novelty, personality variables have been included in the analysis whose relation to prisonization has not yet been studied. The results showed a high reliability value (α =.810) of the scale and that it is a personality variable, the aggression, followed by two variables related to the deprivation model which would explain the prisonization of the Spanish inmates.